Composition and Formation Process of School Management Committees in Lower Dibang Valley district, Arunachal Pradesh: A Comparison with RTE Act, 2009 Norms - Mini Meto,; Dr Tayum Saroh, (International Journal of Scientific Research in Science and Technology, 2025)
The School Management Committee (SMC) is a statutory body responsible for ensuring the effective governance of schools, particularly in government and government-aided institutions. It plays a vital role in school administration, fostering collaboration between teachers, parents, community members to enhance the smooth functioning of schools, share the decision making and quality of education. Its primary responsibilities included overseeing academic performance, managing resources, implementing policies, and addressing the needs of students and staff. By promoting transparency, accountability, and community involvement, the SMC contributes to the overall development of the school, enhancing the quality of education and creating a conducive learning environment. The study highlights the significance of the SMC in bridging the gap between school administration and the community, ultimately driving institutional growth and student success of Lower Dibang Valley district of Arunachal Pradesh.
Keywords: Students; Teachers; Parents; Community Members; SMCs; Lower Dibang Valley; Arunachal Pradesh